Pengaruh Brand Image, Harga Dan Produk Terhadap Loyalitas Pelanggan Dimsum Uma Yumcha - Anita Nurul Cahyani; Olivia Stephanie Sarwono Putri; Rayhan Gunaningrat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The purpose of this research is: (1) to find out what Dimsum Uma Yumcha is in the popular dimsum market in Solo. (2) to find out the affordable prices offered which influence customer loyalty. (3) to find out the product provided has an effect on customer loyalty. In research it is known that Brand Image, Price and Product influence customer loyalty. This research method is quantitative. The data collection technique used in this research is Probability Sampling. The population in this study were all people who consumed Uma Yumcha Dimsum products in Solo Raya City. The research sample consisted of 100 respondents from the Solo Raya community who had consumed ddimsum. Data processing in this research uses SPPS version 25. The research results show that brand image influences customer loyalty. Price affects customer loyalty. products influence customer loyalty.